2022
DOI: 10.3389/fpsyg.2021.794777
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Explanation of Upper Limb Functional Exercise and Its Maintenance in Postoperative Patients With Breast Cancer

Abstract: Background: Upper limb functional exercise (ULFE) has a positive effect on promoting the rehabilitation of upper limb function. However, little is known, about what drives postoperative patients to engage in and even maintain the advised exercises. This study integrated the health action process approach (HAPA) and the theory of planned behavior theory (TPB) to investigate the psychosocial determinants on the initiation and maintenance of ULFE in breast cancer patients. In addition, this study also tests key h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Previous researches are consistent with our outcomes about time after surgery. 4 , 34 , 35 On the one hand, we have shown that with the progression of time and the recovery of upper limb functions, the functional exercise compliance of patients can gradually drop. On the other hand, we have pointed out that at 3 months after surgery, the functional exercise compliance of patients has started to decrease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous researches are consistent with our outcomes about time after surgery. 4 , 34 , 35 On the one hand, we have shown that with the progression of time and the recovery of upper limb functions, the functional exercise compliance of patients can gradually drop. On the other hand, we have pointed out that at 3 months after surgery, the functional exercise compliance of patients has started to decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also show that it is necessary for patients with breast cancer to do upper limb functional exercise within 6 months after surgery, so as to promote upper limb functional rehabilitation. 3 , 4 Besides, according to the study of Zhou et al, a better upper limb function recovery through functional exercise might be helpful for health-related quality of life improvement and reduce the chance for post-surgery breast cancer patient populations to experience pain-induced negative psychological states, fatigue, sleep disturbance, as well as upper limb function disabilities during the rehabilitation process. 2 However, Zhang et al, 4 pointed out that the level of compliance with doing upper limb functional exercise was only moderate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HAPA has also been used in numerous research studies on patients’ physical exercise. Similarly, the HAPA has several limitations; for example, studies have shown that risk perception does not explain the variance of behavior and intention well ( Schwarzer et al, 2007 ; Kaczynski et al, 2008 ; Zhang et al, 2022 ), which means that risk perception is a negligible variable because most exercisers do not necessarily engage in or withdraw from exercise because they perceive the presence of risk. Another limitation is that the HAPA does not include social factors that influence exercise behavior or behavioral intentions ( Chow and Mullan, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The construction of an integrated HAPA-TPB model could improve the prediction of exercise behavior and clarify the specific roles of each moderating variable. Several researchers have integrated and revised the TPB and HAPA in the context of Chinese culture ( Shen et al, 2010 ) and have been able to better explain the relationships among the variables involved in the various stages of physical exercise behavior among Chinese people ( Zhou, 2014 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%